Antibiotic-induced depletion of Clostridium species increases the risk of secondary fungal infections in preterm infants - Huang, Dabin; Li, Huixian; Lin, Yuying; Lin, Jinting; Li, Chengxi; Kuang, Yashu; Zhou, Wei; Huang, Bing; Wang, Ping (Frontiers in Cellular and Infection Microbiology, 2022)
Preterm infants or those with low birth weight are highly susceptible to invasive fungal disease (IFD) and other microbial or viral infection due to immaturity of their immune system. Antibiotics are routinely administered in these vulnerable infants in treatment of sepsis and other infectious diseases, which might cause perturbation of gut microbiome and hence development of IFD. In this study, we compared clinical characteristics of fungal infection after antibiotic treatment in preterm infants. As determined by 16S rRNA sequencing, compared with non-IFD patients with or without antibiotics treatment, Clostridium species in the intestinal tracts of patients with IFD were almost completely eliminated, and Enterococcus were increased. We established a rat model of IFD by intraperitoneal inoculation of C. albicans in rats pretreated with meropenem and vancomycin. After pretreatment with antibiotics, the intestinal microbiomes of rats infected with C. albicans were disordered, as characterized by an increase of proinflammatory conditional pathogens and a sharp decrease of Clostridium species and Bacteroides. Immunofluorescence analysis showed that C. albicans-infected rats pretreated with antibiotics were deficient in IgA and IL10, while the number of Pro-inflammatory CD11c+ macrophages was increased. In conclusion, excessive use of antibiotics promoted the imbalance of intestinal microbiome, especially sharp decreases of short-chain fatty acids (SCFA)-producing Clostridium species, which exacerbated the symptoms of IFD, potentially through decreased mucosal immunomodulatory molecules. Our results suggest that inappropriate use of broad-spectrum antibiotics may promote the colonization of invasive fungi. The results of this study provide new insights into the prevention of IFD in preterm infants.